Hubungan Kepemimpinan Transformasional dan Transaksional dengan Motivasi Bawahan di Militer - Wagimo, -; Ancok, Djamaludin (Faculty of Psychology, Universitas Gadjah Mada, 2005)
The aim of this research is to test the correlations between leadership variable and followers’ motivation in military. There are several hypothesis’ to be tested in this research. (1) There is a significant and positive correlation between both transformational leadership and transactional leadership with followers’ motivation, (2) There is a significant and positive correlation between transformational leadership and followers’ motivation, (3) There is a significant and positive correlation between transactional leadership and followers’ motivation, and (4) The correlation between transformational leadership and followers’ motivation is stronger than the correlation between transactional leadership and followers’ motivation. The subjects of this research are 110 members of Indonesian Military (Bintara and Tamtama) who followed the Setukpa and Setukba Education in Indonesian National Air Force. This research used 2 kinds of questionnaire. The first is motivation questionnaire, and the second is the leadership questionnaire. The results supported all of hypotheses of the study; (1) F-reg =24,660; (2) r = 0,559; (3) r = 0,225; (4) r = 0,559. Keywords: motivation, transactional leadership, transformational leadership.